Transulnar catheterization in patients with ipsilateral radial artery occlusion. Issue 7 (14th March 2013) - Kwan, Tak W.; Ratcliffe, Justin A.; Chaudhry, Muhammad; Huang, Yili; Wong, Sally; Zhou, Xuanjing; Pancholy, Samir; Patel, Tejas
<x xml:space="preserve">Abstract</x> Background The transradial approach to percutaneous coronary intervention (PCI) has recently gained popularity among interventionalists. However, radial artery occlusion (RAO) limits the ability for repeat catheterization. In current practice, transulnar catheterization is thought to be a contraindication in patients with ipsilateral RAO. Methods Seventeen consecutive patients undergoing transulnar catheterization and PCI were reviewed. Each of the patients had clinical follow‐up post‐procedure at days 1, 7, and 30. Results We successfully performed 17 ulnar catheterizations in patients with ipsilateral RAO. All patents were subsequently found to have adequate collaterals from the anterior interosseous branch. One patient developed ulnar artery spasm and another patient developed a forearm hematoma. Overall, no patient suffered any ulnar nerve injury. The ulnar artery was patent both by palpation and by the presence of an adequate plethysmographic signal during follow‐up at days 1, 7, and 30. No patients developed with any signs or symptoms of hand ischemia during follow‐up. Conclusion In patients with RAO, ipsilateral transulnar catheterization may not be an absolute contraindication. Our results suggest that extensive collaterals from the anterior interosseous artery may be the reason for protection against hand ischemia in the setting of RAO. © 2012 Wiley Periodicals, Inc.